Localised Tuneable Composition Single Crystal Silicon-Germanium-on-Insulator for Low Cost Devices. (8th June 2016) - Littlejohns, Callum G.; Dominguez Bucio, Thalia; Nedeljkovic, Milos; Wang, Hong; Mashanovich, Goran Z.; Reed, Graham T.; Gardes, Frederic Y.
Abstract : The realisation of high quality silicon-germanium-on-insulator (SGOI) is a major goal for the field of silicon photonics because it has the potential to enable extremely low power active devices functioning at the communication wavelengths of 1.3  μ m and 1.55  μ m. In addition, SGOI has the potential to form faster electronic devices such as BiCMOS transistors and could also form the backbone of a new silicon photonics platform that extends into the mid-IR wavelengths for applications in, amongst others, sensing and telecoms. In this paper, we present a novel method of forming single crystal, defect-free SGOI using a rapid melt growth technique. We use tailored structures to form localised uniform composition SGOI strips, which are suitable for the state-of-the-art device fabrication. This technique could pave the way for the seamless integration of electronic and photonic devices using only a single, low cost Ge deposition step.